Relative wage structure in Chile, 1957 - 1992: Changes in the structure of demand for schooling - Robbins, Donald (Estudios de Economía, 2016)
It has traditionally been hypothesized that moving from Protectionist to liberalized trade in developing countries (LDCs) will decrease the relative wages of skilled versus unskilled labor (or “relative wages”). Trade liberalization causes “between-industry” shifting of the composition of output across industries towards goods intensive in unskilled labor, decreasing the demand for skilled relative to unskilled labor and relative wages. This paper finds that between-industry demand changes were small. The distribution of employment across industries in 1992 was similar to 1960, and changes in this distribution after 1974 were similar to changes in the 1960’s. These observations suggest that changes in the relative demand for differing schooling levels inside industries or “within –industry” demand changes caused relative wages to rise. This hypothesis is confirmed by evidence of the significant upgrading of schooling and occupations within industries. It is also supported by a decomposition of demand changes into between- and within- industry changes. I conclude that the relative wages of skilled workers increases over the 1975-1990 period in Chile due to within-industry upgrading of schooling and occupational shifts. Theses findings run counter to traditional predictions, and may arise from the indirect effects of trade liberalization leading to economy-wide modernization of production towards more skill-intensive methods. This is consistent with ‘New’ trade theories. In addition to the importance of primary and secondary education policy that have been justly emphasized in recent years, these results suggest that for trade liberalization to be successful and equitable, high and growing levels of university educated workers may be needed.